10 - Nigeria Paralysed: Socio-political Life Under General Sani Abacha: 10.4314/ad.v26i2.22149 - Kgwaikhide, Festus O; Isumonah , Victor Adefemi (Africa Development, 2001)
It is convenient to blame Nigerian civil society for the inconclusive transit to civil rule undertaken by General Ibrahim Badamasi Babangida. But this reason omits the fact that elements of civil society, notably, the Campaign for Democr (CD), a human rights organisation, successfully mobilised Nigerians living in the majo cities in the west of the country (the major economic hub), to stay at home, paralysi economic activities for days and months. The action changed nothing. The devour forces of personal ambition and greed were irresistible. Unlike the popular portrayal civil society in Africa as weak, we argue that General Sani Abacha drove Nigeria unde the wedge of personalist rule in fulfillment of his personal ambition and material gre As a result, the struggle for mere survival became the preoccupation of most Nigeria This experience is here recalled in order to counter the natural tendency to forget ve quickly the pain of the past and at the same time the vital lessons for guarding agains repetition of abuses.